Commodities at a Glance: Special Issue on Gum Arabic - United Nations Conference on Trade; Development (United Nations, 2019)
The series “Commodities at a Glance” aims to collect, present and disseminate accurate and relevant statistical information linked to international primary commodity markets in a clear, concise and reader-friendly format. This issue of “Commodities at a Glance” explores the economic, social and environmental relevance of the gum arabic sector, with a focus on supply, demand, prices and market organization. Gum arabic is the most commercially valuable exudate gum, with wide applications in industries as diverse as food and beverages, pharmaceuticals, cosmetics, and printing. The gum is produced primarily in arid wooded savannas in sub-Saharan Africa, and consumed predominantly by manufacturers in developed and emerging economies. Due to its potential to generate foreign exchange reserves, ensure food security, promote sustainable agriculture and forestry, and combat desertification and climate change, gum arabic is a promising commodity for a number of African countries. However, in order to overcome the current uneven distribution of economic gains along the gum arabic value chain, producing countries must increase local processing and ensure higher compensation for resource-poor gum collectors.